EFEKTIVITAS POWERPOINT MORPH TRANSITION TERHADAP HASIL BELAJAR SISWA SMK PADA MATA PELAJARAN KONSTRUKSI GEOMETRI - Riki Febrianto; Septian Eko Cahyanto; Kriswanto Kriswanto (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
This study aims to analyze the effectiveness of learning media based on the Morph Transition feature in Microsoft PowerPoint on students’ learning outcomes in the Geometric Construction subject at SMKN 1 Semarang. The development of the learning media was carried out by referring to the principles of the Cognitive Theory of Multimedia Learning (CTML). Before implementation, both the learning media and the research instruments were validated by six validators and obtained an average feasibility score of 86.1%. This study employed a quasi-experimental design using a pretest-posttest control group approach involving 62 students, consisting of 32 students in the control class and 30 students in the experimental class. The results showed that the average posttest score of the experimental class reached 92.29, which was higher than that of the control class with an average score of 85.65. The Independent Sample T-Test results also indicated significant differences in posttest scores (t = −2.406; sig. = 0.019) and N-Gain scores (t = −3.703; sig. = 0.000). In addition, Cohen’s d effect size values of 1.367 for the posttest and 1.710 for the N-Gain demonstrated that the learning media had a strong practical effect on improving students’ learning outcomes. Nevertheless, research on the use of the Morph Transition feature in Geometric Construction learning in mechanical engineering vocational schools remains relatively limited. Therefore, the findings of this study reinforce the importance of developing similar learning media, particularly for procedural subjects in vocational high school environments. ABSTRAK Penelitian ini bertujuan untuk menganalisis efektivitas media pembelajaran berbasis Morph Transition pada Microsoft PowerPoint terhadap hasil belajar siswa pada mata pelajaran Konstruksi Geometri di SMKN 1 Semarang. Pengembangan media dilakukan dengan mengacu pada prinsip Cognitive Theory of Multimedia Learning (CTML). Sebelum digunakan, media pembelajaran dan instrumen penelitian telah divalidasi oleh enam validator dan memperoleh rata-rata tingkat kelayakan sebesar 86,1%. Penelitian ini menggunakan desain quasi-experimental tipe pretest-posttest control group dengan melibatkan 62 siswa yang terdiri atas 32 siswa kelas kontrol dan 30 siswa kelas eksperimen. Hasil penelitian menunjukkan bahwa rata-rata nilai posttest kelas eksperimen mencapai 92,29, lebih tinggi dibandingkan dengan kelas kontrol yang memperoleh rata-rata 85,65. Hasil Independent Sample T-Test juga menunjukkan adanya perbedaan yang signifikan pada nilai posttest (t = −2,406; sig. = 0,019) serta N-Gain Score (t = −3,703; sig. = 0,000). Selain itu, nilai effect size Cohen’s d sebesar 1,367 pada posttest dan 1,710 pada N-Gain menunjukkan bahwa media pembelajaran tersebut memiliki pengaruh praktis yang kuat terhadap peningkatan hasil belajar siswa. Meskipun demikian, penelitian mengenai penggunaan fitur Morph Transition dalam pembelajaran Konstruksi Geometri pada SMK Teknik Mesin masih tergolong terbatas. Oleh karena itu, temuan penelitian ini memperkuat pentingnya pengembangan media pembelajaran serupa, khususnya untuk mata pelajaran prosedural di lingkungan SMK.